A rare case of spontaneous gastric perforation in an adolescent - R., Vasuki; P. S., Arun; Moothedath, Rajesh Menon (International Surgery Journal, 2018)
Incidence of Peptic ulcer perforation in children and adolescents are very rare. Perforated gastric ulcer is extremely rare with only handful of cases reported worldwide in the same age group. Pneumoperitoneum and peritonitis due to gastric perforation is a very rare presentation in children and adolescents and it can often be overlooked with disastrous consequences. Even though in young patients, peptic ulcerations can happen in association with H. pylori infection, secondary to medications like non-steroidal anti-inflammatory agents, corticosteroids, rarely due to Zollinger Ellison syndrome, related to stress, post burns or head trauma it is seldom common. Among perforations gastric perforation is very rare. Here we discuss a case of 15-year-old school student who presented with acute abdominal pain and features of peritonitis which we initially thought probably due to perforated appendix but turned out to be a gastric perforation. Plain radiograph of the abdomen showed pneumoperitoneum. When an emergency midline laparotomy was performed, we found a perforation in gastric antrum anteriorly with peritonitis which was treated by thorough decontamination and Graham's live omental patch closure. H. Pylori tests were negative. At a time when acute presentation of peptic ulcerations or perforation as its complication is decreasing in incidence worldwide, this case has come as an eye opener. Thus, perforated gastric/duodenal ulcer in pediatric and young adult patient should not be overlooked in a young patient presenting with acute abdomen. Many times, there is no clear etiology and then it is spontaneous perforation. Emergency surgical management is the preferred mode of treatment.